2012
DOI: 10.1055/s-0032-1311549
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Endothelial Vascular Function of Saphenous Vein Grafts after Long-Time Storage with a Recently Developed Potassium-Chloride and N-Acetylhistidine Enriched Storage Solution

Abstract: Vessel functions comprising contraction, endothelium-dependent and -independent vasodilatation are significantly reduced following 24 hours of cold storage in NaCl. After 96 hours of storage in NaCl these functions are nearly totally abolished. TiProtec is able to largely reduce this loss of function during cold storage. Therefore, TiProtec is a feasible option for longer term storage of saphenous vein grafts in CABG vessel and transplant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Vessel preparation was performed according to a slightly modified method as previously described (Wilbring et al, 2013; Kopaliani et al, 2014; Bosche et al, 2016). In brief, male CD57 mice 10 weeks of age (Charles River Laboratories, Sulzfeld, Germany) were sacrificed by cutting off the upper cervical spinal cord under deep anesthesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessel preparation was performed according to a slightly modified method as previously described (Wilbring et al, 2013; Kopaliani et al, 2014; Bosche et al, 2016). In brief, male CD57 mice 10 weeks of age (Charles River Laboratories, Sulzfeld, Germany) were sacrificed by cutting off the upper cervical spinal cord under deep anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Vessel function was assessed according to the method of Mulvany and Halpern (1977) as described previously (Wilbring et al, 2013; Kopaliani et al, 2014; Bosche et al, 2016). Briefly, aortic and cerebral vessel grafts (2 mm in length and 0.5–0.6 or 1.2–1.4 mm internal width, respectively) were transferred to carbogen equilibrated phosphate saline solution (PSS; in mmol/L: 119 NaCl, 4.7 KCl, 2.5 CaCl 2 , 1.17 MgSO 4 , 1.18 KH 2 PO 4 , 25 NaHCO 3 , 5.5 glucose, 0.027 EDTA) and equilibrated for 30 min at 37°C and subsequently mounted in a myograph (DMT-610 M, Power Laboratory/400; AD-Instruments, Spechbach, Germany) for isometric force measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Saphenous vein segments were studied in a four chamber Myograph as published previously [16]. Vessel rings of 2 mm length were placed on stainless steel hooks (diameter 200 m) in a 5 ml tissue bath with physiological saline solution (PSS: in mmol/l: Glucose 5.5, Na + 144, Cl − 128.7, H 2 PO 4 − 1.18, SO 4 2− 1.17, HCO 3 − 25, K + 5.9, Mg 2+ 1.17, Ca 2+ 2.5, EDTA 0,027.))…”
Section: Vasomotor Function Analysismentioning
confidence: 99%
“…For fluororescence detection of nucleotides derivatisation with chloracetaldehyd to their 1,N 6 -etheno-analouges was performed as described previously (16). 143 l neutralized sample were mixed with 51 l of citrate-phosphate-buffer (0.1 mol/l Na-citrate, 0.2 mol/l Na 2 HPO 4 ) for pH adjustment to pH = 4.…”
Section: Determination Of Energy Chargementioning
confidence: 99%
“…Although Gundry et al 12 showed that storage in a saline solution had deleterious effects on endothelial function compared with preservation in autologous blood, other studies 13-18 aiming to substantiate these findings have shown conflicting results. Other studies 9,15,16,19-23 have investigated the effect of storage in various buffered saline solutions on vessel wall tension and endothelial function in discarded vein graft segments and overall have shown improved endothelial function after preservation in a buffered saline storage solution compared with saline- and/or blood-based media.…”
Section: Discussionmentioning
confidence: 99%